Optimization of Thirst Management on CKD Patients Undergoing Hemodialysis by Sipping Ice Cube - Yunie Armiyati; Khoiriyah Khoiriyah; Ahmad Mustofa (Universitas Muhammadiyah Semarang, 2019)
Excess fluid is a major problem in patients with Chronic Kidney Disease (CKD). CKD patients undergoing hemodialysis must keep limiting fluid intake during the interdialysis period so that excess fluid does not occur. Consequently limiting fluid intake arises thirst and will affect fluid restriction compliance. Management of thirst that can be done in hemodialysis patients, among others, suck ice cubes, gurgling the ripe water and gurgling with mouthwash, each of which has a different action against patients thirst. The purpose of this study was to compare the three interventions